Coping mechanisms used by the families of mental health care users in Mahikeng sub-district, North West province - Tshepang P. Modise; Isaac O. Mokgaola; Leepile A. Sehularo (AOSIS, 2021)
Background: Families of the mental health care users (MHCUs) face different challenges in dealing with, supporting and caring for MHCUs on a daily basis. The divergent coping mechanisms that the family members use aim to lower the negative, psychological and emotional impact of the stress. These include: escape, avoidance and denial. Aim: To explore, describe and contextualise coping mechanisms used by the families of MHCUs and to suggest recommendations for improving their coping mechanisms in Mahikeng sub-district, North West province (NWP), South Africa. Setting: The study was conducted in three community health centres in Mahikeng sub-district, NWP, South Africa. Methods: A qualitative-exploratory-descriptive and contextual research design was used. Non-probability convenience and purposive sampling techniques were used to select participants. WhatsApp video calls were used to collect data which were analysed following Creswell's six steps of qualitative data analysis. Results: The study established three themes namely; challenges experienced by the family members, coping mechanism used by the family members, and suggestions for improvement in the coping mechanisms for the family members. Conclusion: The findings of this study show that the family members of MHCUs are faced with different challenges. Some of the coping mechanisms used by the family members are insufficient and require improvement to enable them to cope effectively. When the coping mechanisms of the family members of MHCUs are improved, their well-being and that of the MHCUs might improve significantly. Contribution: The findings of this study provides information that may be used to improve the coping mechanisms of the families of MHCUs in the NWP, South Africa.